Pembentukan Komposit Zeolit X - Bayerit dari Perlakuan Abu Sekam Padi dan Aluminium Kemasan Produk Pangan dalam Larutan NaOH Teknis pada Suhu Ruangan - Dede Suhendar; Luthpiansyah; Budy Frasetya Taufik Qurrohman; Yusuf Rohmatulloh (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
Various research efforts have been carried out to obtain efficient zeolite synthesis methods, including the use of waste as the main ingredient or carried out at room temperature. One type of zeolite that has been synthesized at room temperature is zeolite X (ZX) within a minimum of 28 days using synthetic chemicals. The purpose of this study is to explore how ZX can be formed from waste materials and NaOH technical grade solution (TGS) at room temperature for 40 days without stirring treatments. The waste materials are rice husk ash from the traditional red brick industry, aluminum beverage cans, and food packaging aluminum waste. The materials were homogeneously mixed with the NaOH TGS in such a way as to produce a mixture with a mole ratio of 7.23Na2O : 0.26Al2O3 : 1SiO2 : 280H2O, with mole ratios of Na2O/H2O and Al2O3/SiO2 that were 30% higher than the literature for ZX synthesis, respectively. The results of characterization showed that the treatment yield was ZX along with the presence of the bayerite phase, which had been formed since the 20-day observation period. The use of excess Na2O/H2O and Al2O3/SiO2 mole ratios in this study impacts the formation of bayerite first and the ability of dissolved silica to condense, thus slowing the crystallization of ZX. The result of this study led to the new finding that zeolite-bayerite composite can be synthesized directly in a simple, inexpensive, and environmentally friendly manner, where the composite materials have been reported as catalysts and adsorbents.